ISOLATION OF STAPHYLOCOCCUS PASTEURI IN THE CULTURED RUSSIAN STURGEON (ACIPENSER GUELDENSTAEDTII) IN BULGARIA - A. Atanasoff; C. Urku (Journal of Animal and Plant Sciences, 2022)
The present study describes the first case of staphylococcosis causing Staphylococcus pasteuri in Russian sturgeon (Acipenser gueldenstaedtii) in Bulgaria. Clinically, diseased three sturgeons showed hemorrhagic ulcerative skin lesions at the all body surface and internally hyperemia and hemorrhages in the visceral organs and muscle, necrosis in the liver and swollen spleen were observed. Biochemical tests and Vitek 2 system were used to determine the phenotypic characteristics of isolated bacteria in samples taken from liver, spleen and kidney. The isolated bacteria were identified as Staphylococcus sp. Furthermore, 16S rRNA gene of one isolate was partially sequenced and showed 98% identity with the Genbank sequences of Staphylococcus pasteuri. The isolates were determined to be sensitive to sulfamethoxazole-trimethoprim, enrofloxacin and florfenicol, they were resistant to erythromycin, ampicillin and ciprofloxacin. Histopathologically, hemorrhage and lymphocyte groups in the epicardium; intense necrotic areas in the hearth; melonomacrophage centers, lymphocyte infiltration around the necrotic hepatocyte cells; necrosis in the kidney; hyperemia and intense hemorrhagic areas in the spleen and melonomacrophage foci, hyperplasia and increase in the number of the goblet cells in the gills were observed. This study represents the first report of S. pasteuri isolation and identification as an agent of diseased Russian sturgeon.
Keywords: Russian sturgeon; Staphylococcus pasteuri; 16S rRNA gene; antibiogram; histopathology